Disruption and Experimentation: The interplay between printed newspapers and their online websites - Dodd, Andrew; Ewing, Scott; Haley, Ken (Journal of Telecommunications and the Digital Economy, 2020)
This paper is in two parts. It seeks to contextualise the myriad changes occurring to newspaper websites through consideration of a body of literature that explores the implications of the media disruption caused in part by the continual rise of digital media. The paper then reports on a study of six Australian newspaper websites, which were all analysed on the same day in July 2014. The study focused on several elements of each website, including their architecture, story form and content, as well as their business models and use of multimedia. This analysis seeks to assess how newspaper websites are adapting to change and how they are relating to both their own readers and to the printed versions of the same masthead.